Presentation, Treatment, and Prognosis of Secondary Melanoma within the Orbit - Rose, Anna M.; Cowen, Sophie; Jayasena, Channa N.; Verity, David H.; Rose, Geoffrey E. (Frontiers in Oncology, 2017)
Background: Ocular melanoma is a rare but often deadly malignancy that arises in the uvea, conjunctiva or orbit. Uveal melanoma is the most common type, with conjunctival melanoma being the second most frequently observed. Melanoma accounts for 5-10% of metastatic or secondary orbital malignancies, but only a minute proportion of primary orbital neoplasia. The aim of the study was to characterise the clinical presentation, treatment and prognosis in patients presenting with melanoma metastatic to, or secondary within, the orbit. Methods: A retrospective cohort study of patients presenting to a tertiary referal orbital unit from 1982-2016 was performed. Eighty nine patients with biopsy proven diagnosis of melanoma wihtin the orbit were included in the study. The clinical notes, radiological imaging, histology, surgical notes and outcome data for the patients were reviewed. The main outcome measures of interest were the interval between primary malignant melanoma and orbital presenation, survival after orbital presentation, and clincal parameters (such as gender, age at presentation and treatment approach). Results: The commonest primary source of tumour was choroidal melanoma, with conjunctival and cutaneous melanomas being relatively common; eyelid and naso-sinus tumours occurred in a few cases. The mean age at presentation with orbital disease was 65 years (31-97 years). The interval between primary malignancy and orbital disease (either local spread/recurrence or true metastatic disease) showed wide variability, with almost one third of patients having orbital disease at the time of primary diagnosis, but others presenting many years later; indeed, the longest orbital disease-free interval was over 34-years. Twenty-three patients were considered to have had late orbital metastases – that is, at more than 36 months after primary tumour. The median survival following presentation with orbital involvement was 24 months. Patients with tumours of cutaneous origin had worst survival, whilst conjunctival tumours had the best prognosis. Conclusions: A high index of suspicion for orbital recurrence should be maintained in any patient with prior history of melanoma, however distant the primary tumour is in site or time. Furthermore, giving a prognosis for orbital melanoma remains problematic due to highly variable survival, and further investigation will be necessary to understand